What's on your mind? Facebook technology literacy and storying among selected parents and children of two urban poor communities - Doctor, Jesse David Cabanatuan 1996- (College of Mass Communication, University of the Philippines, 2017)
" This study inquired into the Facebook literacy states of parents and children of Daantubo, Quezon City and Sta. Cruz, Manila as well as their Facebook storying interactions with each other. The urban poor is a marginalized sector in the Philippines. With the advent of globalization, technological advancements and internet democratization, this study explored if this sector was being left out or whether it was able to adapt with the changes in technology. The researcher utilized Portus's (2005) Social Construction of Technology Theory and Cruz and Snider's (2009) Storying with Technology Approach as guides and consequently conducted four focus groups discussions, sixteen focus interviews and five key informant interviews to meet the research objectives. Findings of the study showed that the urban poor under study manifested, acquired and reached in various stages the three FB literacy states, namely: awareness and acquisition, interpretive and critical. Children were more expert in the awareness and acquisition level while a few of the parents were more on interpretive and critical states. These literacies, often in the form of knowledge and realities, were then passed on by both of them to each other through a process called storying. Informant's literacies and storying behaviors were greatly affected by individual experiences and motivations and by the influence of their social circles."